The effectiveness of using augmented reality technology in raising the on learning mathematics among students with learning difficulties in the third grade of primary school in Makkah Al-Mukarramah - Bagabas, Hanan Ali; Asiri, Lina Nayef (Journal of Curriculum and Teaching Methodology, 2025)
The study aimed to reveal the effectiveness of using augmented reality technology on learning mathematics among third-grade primary school students with learning difficulties in Makkah Al-Mukarramah. The study used the quasi-experimental approach with (one group), and the study sample was selected third-grade primary school students with learning difficulties in mathematics in Makkah Al-Mukarramah, numbering (9) students., the study tools were an achievement test and a scale of motivation to learn mathematics using augmented reality technology. The results showed that there were statistically significant differences between the average scores of third-grade primary school students with learning difficulties in the pre- and post-test of academic achievement, in favor of the post-test, attributed to the use of augmented reality technology, and the effectiveness of using augmented reality technology on academic achievement in learning mathematics among third-grade primary school students with learning difficulties. The results also showed statistically significant differences between the average scores of third-grade primary school students with learning difficulties in the pre- and post-test of mathematics learning motivation scale, in favor of the post-test, attributed to the use of augmented reality technology, and the effectiveness of using augmented reality technology in mathematics learning motivation among third-grade primary school students with learning difficulties in Makkah Al-Mukarramah. The study reached several recommendations, including the necessity of applying augmented reality techniques to teach mathematics to female students with mathematics learning difficulties, at different levels of education.
Keywords: augmented reality; mathematics; learning difficulties